Islamic Religious Education Models in Preventing Negative Behaviors of Youth and Adolescents - Sukino Sukino; Septiasari Putri Utami (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This study offers explicitly new knowledge about socialization and internalization of religious values that form noble morals, which are solutions to prevent malicious behavior in the younger generation. This study uses a sociological approach with a qualitative narrative. Data were collected using interviews and observations; the primary data sources were religious leaders, youth community leaders, and youth in the village of Kampung Jawa Tengah. The analysis was carried out from entering the research field, data reduction, and verification. At the same time, the data validity technique used triangulation and member checks. This research concludes the first two things that deviant behavior such as stealing, drinking, drugs, and gambling have still occurred in the village of Kampung Jawa Tengah in the last three years; the trigger factors are poverty, unemployment, and weak parental control. The educational model, which is a strategy to prevent deviant behavior, is strengthening religious knowledge through various activities and strengthening tolerance attitudes in adolescents through arts and sports activities so that empathy grows to participate in avoiding criminal behavior among teenagers.